Քերականական–ձևաբանական նորմերի խախտումները համացանցային հայերենում - Վարդանյան, Նարինե (Զանգակ հրատ.)
Speakers not always maintain all grammatical norms in oral speech. However, before the Internet came into being the written public speech was predominantly based on preservation of Armenian language norms, which was largely a subject to censorship and editing. Today the situation has dramatically changed. Alongside with numerous mistakes (spelling, punctuation, lexical), a great variety of cases regarding the violation of grammatical norms are evident. The given article is dedicated to the study of these cases. Particularly, the mistakes concerning the plural, the incorrect usage of dates, pronouns and link words, cases of violation of verbal norms, as well as penetration of some common expressions of everyday language into written speech have been considered. В устной речи говорящий не всегда поддерживается всех грамматических правил. Однако письменная публичная речь до распространения Интернета строилась согласно нормам армянского языка, в значительной степени подвергаясь цензуре и редактированию. Сегодня ситуация резко изменилась. Рядом со множеством ошибок (орфографических, пунктуационных, лексических) стали появляться многочисленные примеры нарушения грамматических норм. Этим вопросам посвящена данная статья. В частности, нами рассмотрены случаи ошибочного употребления форм множественного числа, неправильное использование числительных и местоимений, неверное использование предлогов, случаи нарушения глагольных форм, а также проникновение в письменный язык некоторых выражений, характерных для повседневной бытовой речи.
Keywords: Խոսակցական լեզու